State-Dependent Modulation of Visual Evoked Potentials in a Rodent Genetic Model of Electroencephalographic Instability - Grønli, Janne; Schmidt, Michelle A.; Wisor, Jonathan P. (Frontiers in Systems Neuroscience, 2018)
Despite normal sleep timing and duration, Egr3-deficient mice exhibit electroencephalographic (EEG) characteristics of reduced arousal, including elevated slow wave (1-4 Hz) activity during wakefulness. Here we show that these mice exhibit state-dependent instability in the EEG. Intermittent surges in EEG power were found in Egr3-deficient mice during wakefulness and rapid eye movement sleep, most prominently in the beta (15-35 Hz) range compared to wild type mice. Such surges did not coincide with sleep onset, as the surges were not associated with cessation of electromyographic tone. Cortical processing of sensory information by visual evoked responses (VEP) were found to vary as a function of vigilance state, being of higher magnitude during slow wave sleep than wakefulness and rapid eye movement sleep. VEP responses were significantly larger during quiet wakefulness than active wakefulness, in both Egr3-deficient mice and wild type mice. EEG synchronization in the beta range, previously linked to the accumulation of sleep need over time, predicted VEP magnitude. Egr3-deficient mice not only displayed elevated beta activity, but in quiet wake, this elevated beta activity coincides with an elevated evoked response similar to that of animals in slow wave sleep. These data confirm that a) visual evoked potentials vary as a function of vigilance state, and b) beta activity in the EEG is a predictor of state-dependent modulation of visual information processing. The phenotype of Egr3-deficient mice indicates that Egr3 is a genetic regulator of these phenomena.